Teaching quality as students’ course experience determinant: evidence from Malaysian higher education institutions - Paramboor, Jafar; Musah, M. B.; Aldaba, A. M; Solih, M; Tunku Ahmad, Tunku Badariah (Department of Educational Management, Planning & Policy, Faculty of Education, University of Malaya, 2023)
The purpose of this study was to investigate the underlying factors of course experience in six selected Malaysian public higher education institutions. The relationship between Teaching Quality Initiative (TQI), the mediating factor, Quality Assurance Initiative (QAI), and the dependent variable, Course Experience (CE) was examined. The research used a survey instrument and employed simple random sampling technique with a quantitative research design. Statistical techniques including SPSS version 20.0, Confirmatory Factor Analysis (CFA), and a full-fledged Structural Equation Modeling (SEM) with Analysis of Moment Structures (AMOS) software version 22.0 were used to analyze the received questionnaire, address the research questions, and test the hypotheses. TQI represented two distinct factors, i.e., enthusiasm and group interaction; QAI was indicated by three dimensions, quality practices, facilitators, and obstacles; and CE represented three variables, student empowerment, good teaching, and appropriate assessment. The result also demonstrated the validity and reliability of each factor. The proposed theoretical model of course experience was tested using SEM technique. The results were indicative of the direct causal effect of TQI and QAI on CE, as well as the indirect causal effect of TQI on CE through the mediation of QAI.